KIAT MEMBENTUK PERATURAN DESA YANG BAIK - Susanto, Susanto; Isnaeni, Beli; Bachtiar, Bachtiar; Prastiwi, Dian Eka; Setiawan, Tato (Universiitas Pamulang, 2021)
ABSTRACT The Village Regulation is stipulated by the Village Head after being discussed and agreed upon with the Village Consultative Body which is a legal and policy framework in the administration of Village Government and Village Development. The stipulation of Village Regulations is a description of the various powers that the Village has with reference to the provisions of higher laws and regulations. So that as a legal product, the Village Regulation must not conflict with higher regulations and may not harm the public interest. One of the reasons for the promulgation of Law Number 6 of 2014 concerning Villages is the recognition that villages have rights of origin and traditional rights in regulating and managing the interests of the local community and playing a role in realizing the ideals of independence based on the 1945 Constitution of the Republic of Indonesia. This is because the recognition of the village as an autonomous region makes the village have a major role in managing, empowering and advancing the available resources, both natural and human resources. So that in the end they are able to move the wheels of development which must be accompanied by an awareness of the understanding of the spirit of autonomy for all village residents and the capacity of the apparatus as well as the community in understanding governance. Village / Traditional Village Institutions, namely Village / Traditional Village Government institutions consisting of Village / Traditional Village Governments and Village / Traditional Village Consultative Bodies, Village Community Institutions, and traditional institutions. The Village / Traditional Village Head or what is referred to by any other name is the head of the Village / Traditional Village Administration who leads the administration of the Village Government. The Village / Traditional Village Head or what is referred to by any other name has an important role in his position as an extension of the state close to the community and as a community leader. Tri Dharma Perguruan Tinggi is the vision of all tertiary institutions in Indonesia which consists of education and teaching, research and development, and community service. As an effort to realize this vision, the Pamulang University Master of Law study program by involving lecturers and students has held Community Service in the form of providing technical guidance to village heads and the Kalimati Village Consultative Body, Adiwerna District in drafting village regulations to be carried out in Kalimati village, Adiwerna District, Tegal Regency. Keywords: Technical Guidance, and Village Regulations ABSTRAK Peraturan Desa ditetapkan oleh Kepala Desa setelah dibahas dan disepakati bersama Badan Permusyawaratan Desa merupakan kerangka hukum dan kebijakan dalam penyelenggaraan Pemerintahan Desa dan Pembangunan Desa. Penetapan Peraturan Desa merupakan penjabaran atas berbagai kewenangan yang dimiliki Desa mengacu pada ketentuan peraturan perundang-undangan yang lebih tinggi. Sehingga sebagai sebuah produk hukum, Peraturan Desa tidak boleh bertentangan dengan peraturan yang lebih tinggi dan tidak boleh merugikan kepentingan umum. Salah satu daru alasan di buatnya Undang-undang Nomor 6 Tahun 2014 tentang Desa adalah pengakuan bahwa Desa memiliki hak asal usul dan hak tradisional dalam mengatur dan mengurus kepentingan masyarakat setempat dan berperan mewujudkan cita-cita kemerdekaan berdasarkan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 Hal ini disebabkan karena dengan diakuinya desa sebagai sebuah daerah otonom menjadikan desa memiliki peran utama dalam mengelola, memberdayakan dan memajukan sumber daya yang tersedia, baik sumber daya alam maupun sumber daya manusia. Sehingga pada akhirnya mampu menggerakkan roda pembangunan yang harus diiringi kesadaran akan pemahaman spirit otonomi bagi seluruh penggerak warga desa dan kapasitas perangkat juga masyarakat dalam memahami tata kelola pemerintahan. Kelembagaan Desa/Desa Adat, yaitu lembaga Pemerintahan Desa/Desa Adat yang terdiri atas Pemerintah Desa/Desa Adat dan Badan Permusyawaratan Desa/Desa Adat, Lembaga Kemasyarakatan Desa, dan lembaga adat. Kepala Desa/Desa Adat atau yang disebut dengan nama lain merupakan kepala Pemerintahan Desa/Desa Adat yang memimpin penyelenggaraan Pemerintahan Desa. Kepala Desa/Desa Adat atau yang disebut dengan nama lain mempunyai peran penting dalam kedudukannya sebagai kepanjangan tangan negara yang dekat dengan masyarakat dan sebagai pemimpin masyarakat. Tri Dharma Perguruan Tinggi merupakan visi dari seluruh perguruan tinggi di Indonesia yang terdiri dari pendidikan dan pengajaran, penelitian dan pengembangan, serta pengabdian kepada masyarakat. Sebagai upaya untuk mewujudkan visi tersebut, Program studi Magister Hukum Universitas Pamulang dengan melibatkan Dosen dan para Mahasiswa telah mengadakan Pengabdian Masyarakat dalam bentuk memberikan Bimbingan teknis kepada kepala desa dan Badan Permusyawaratan Desa Kalimati, Kecamatan Adiwerna dalam penyusunan Peraturan desa yang akan dilakukan di desa Kalimati, Kecamatan Adiwerna, Kabupaten Tegal. Kata Kunci: Bimbingan Teknis, dan Peraturan Desa